Seismic pounding mitigation of asymmetric-plan buildings by using viscoelastic links. (February 2022) - Ahmadi Taleshian, Hamed; Mirzagoltabar Roshan, Alireza; Vaseghi Amiri, Javad
Abstract: Connection of adjacent buildings with viscoelastic links (VE) has been proved to be an efficient method for preventing or at least attenuating the structural collisions during earthquakes. The efficiency of this pounding mitigation method was extensively studied in the past, mostly based on assuming a two-dimensional problem without addressing the effects of plan irregularities. In this paper, the effect of VE links between adjacent asymmetric-plan buildings is studied in detail. First, two adjacent one-story models with various structural as well as link-wise dynamic parameters are analyzed under white-noise input. The inelastic behavior of the adjacent buildings is also taken into account. The response of two adjacent 5 story buildings is then evaluated under the actual earthquake record to validate the findings obtained under white-noise analysis. Results demonstrate that not only plan asymmetries do not necessarily lead to higher responses compared to the symmetric adjacent buildings, but the linked-to-unlinked response ratio would be efficiently reduced by providing supplemental damping in the link elements. As the link stiffness decreases, the reduction in the relative displacement of the buildings due to supplemental damping could be up to 80% and even more. Results also reveal that it is possible to obtain a dominant modal damping ratio up to twice than that in symmetric plans for certain plan eccentricities.